Cu2+ ions inducing the growth of porous Co3O4 nanospheres as high-capacity supercapacitors. Issue 24 (28th June 2015) - Liu, Rongmei; Jiang, Zixiang; Liu, Qi; Zhu, Xiandong; Chen, Weiye
<x xml:space="preserve">Abstract</x> Porous Co3O4 nanospheres were successfully synthesized using Cu2+ ions as structure-inducing agents, which exhibit good capacitive properties.